Analisis Finansial Usaha Tambak Kepiting Bakau (Scylla serrata) dan Ikan Kakap Putih (Lates calcarifer) di Kampung Sentosa Barat Lingkungan 20 Kelurahan Sicanang Kecamatan Medan Belawan - Dewi Susanty; Pindi Patana; Febrina Arli (AQUACOASTMARINE, 2016)
Sicanang Village has a very potential aquacultue to be developed and support the farmer’s welfare. This research aims to analyze the financial value of Mangrove Crab and Seabass. It was held for two months from March to April 2016 in West Sentosa Village Area 20, Sicanang Village, Medan Belawan District. It used slovin formula and purposive sampling method. The result showed Mangrove Crab farming is more profitable for further improvement than Seabass farming which had a various issues and considered less worthy to develop. This is proved on the B/C ratio result of Mangrove Crab is 2.46, meanwhile Seabass only 0.93.Keywords : Financial Analysis, Fishpond, Income, Lates calcarifer, Scylla serrata